4CPS-016 Clinical investigation of adverse drug reactions in the treatment with non-vitamin K oral anticoagulants. (March 2019) - di Castri, L; Gatti, F; Isabella, R; Rebecca, C; Seccaspina, C; Ferrari, S; de Masi, A
Abstract : Background: The direct oral thrombin inhibitor (dabigatran) and the inhibitors of the X activated factor (rivaroxaban, apixaban and edoxaban) represent the pharmacological class of non-vitamin K oral anticoagulants (NOACs). In clinical practice this class of drugs can be utilised in: nonvalvular atrial fibrillation with one or more risk factors, prevention of thromboembolic venous events in adult patients undergoing hip or knee elective surgery, treatment of deep venous thrombosis, pulmonary embolism (PE) and in the prevention of recurring DVT and PE in adults. Purpose: The main aim of this study is to describe the suspected adverse drug reactions (ADRs) that have been observed in cases of anticoagulant therapies based on NOACs in our hospital. Material and methods: All reports produced between 1 January 2017 and 31 August 2018 have been processed from the pharmacovigilance national net (RNF) and analysed. Using pivot tables, information regarding demographic characteristics of the patients, the suspected active ingredient, seriousness, severity and the MedDRA terms of adverse drug reactions, have been extracted. Results: In the period under examination, 28 ADRs have been observed and added to the RNF: nine related to Dabigatran, eight relative to Apixaban, seven to Rivaroxaban and four to Edoxaban. The demographic distribution shows a slight prevalence of the female gender (71%) and higher incidence rates in patients between 70 and 80 years of age. Five are the ADR signalled as severe, two of which presented the haemorrhage MedDRA term. Twenty-three are the ADR signalled as not severe. The most common adverse reactions are itch, erythema and heartburn. Most ADRs have been reported by the Vigifarmaco web platform. The most common source appears to be the Physicians Clinic (23 ADRs), while the rest of the signalling (five ADRs) comes from general practitioners. Conclusion: The post-marketing phase is a sensitive aspect of the research on the safety profile of drugs. A greater involvement of all health professionals, in particular general practitioners, is a priority in order to implement the surveillance of patients treated with NOACs, in order to improve knowledge on the safety profile of drugs. References and/or acknowledgements: Safety profile of the direct oral anticoagulants. No conflict of interest.